2018
DOI: 10.1038/s41564-018-0302-8
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive acquisition of CRISPR memory driven by inter-species mating of archaea can limit gene transfer and influence speciation

Abstract: Summary CRISPR-Cas systems provide prokaryotes with sequence-specific immunity against viruses and plasmids, based on DNA acquired from these invaders, known as spacers. Surprisingly, many archaea possess spacers that match chromosomal genes of related species, including those encoding core housekeeping genes. By sequencing genomes of environmental archaea isolated from a single site, we demonstrate that inter-species spacers are common. We show experimentally by mating Haloferax volcani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 57 publications
5
32
0
Order By: Relevance
“…We do not know which genes were targets in these assays and further studies will help to better understand the disadvantages of expressing such CRISPR-Cas system in BMB1685. While the inter-species targeting spacers has proposed may limit inter-species HGT [41]. Therefore, the large numbers of intra-species targeting may limit the HGT among strains in the B. cereus group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not know which genes were targets in these assays and further studies will help to better understand the disadvantages of expressing such CRISPR-Cas system in BMB1685. While the inter-species targeting spacers has proposed may limit inter-species HGT [41]. Therefore, the large numbers of intra-species targeting may limit the HGT among strains in the B. cereus group.…”
Section: Discussionmentioning
confidence: 99%
“…S2 and Dataset 1). It has been reported that the inter-species targeting spacers have a negative effect on mating success in Archaea and may limit inter-species HGT [41].…”
Section: Crispr Locus Analysis and Its Distribution Among B Cereus Gmentioning
confidence: 99%
“…It is possible that the presence of RmeRMS in H. volcanii may prevent the transfer of genetic material from H. mediterranei to H. volcanii due to exposed RmeRMS sites. It is also possible that the lower interspecies mating efficiency is due to H. mediterranei containing CRISPR spacers which target the genome of H. volcanii, since interspecies mating efficiency is further reduced when a CRISPR is added to H. mediterranei which is specifically targeted by H. volcanii (Turgeman-Grott et al, 2019). Future interspecies mating experiments in which H. volcanii ΔRM derivative strains are crossed with H. mediterranei could elucidate the impact of RM systems on mating efficiencies between these two species.…”
Section: Discussionmentioning
confidence: 99%
“…These spacer sequences are used to produce RNAs known as crRNAs, which interact with Cas proteins to target and degrade invasive, foreign elements (Koonin et al, 2017). CRISPR-Cas systems have been identified in halobacterial species such as H. volcanii and H. mediterranei (Li et al, 2013;Maier et al, 2019), and research has indicated that these systems can limit interspecies mating between H. volcanii and H. mediterranei when the chromosome of one species is designed to be targeted by the partner species, although they do not act as total barriers to recombination (Turgeman-Grott et al, 2019). The glycosylation of surface glycoproteins has also been observed to affect mating in H. volcanii.…”
Section: Introductionmentioning
confidence: 99%
“…It was discovered that many spacers match chromosomal genes of related species. Such spacers could be obtained during inter‐species mating, suggesting that CRISPR‐Cas can be used to control this route of horizontal gene transfer and might also influence microbial speciation . Israela Turgeman‐Grott also from the Gophna lab reported on the identification of a novel haloarchaeovirus for Haloferax volcanii 48N.…”
Section: Natural Crispr‐cas Functions Within Microorganismsmentioning
confidence: 99%